2019
DOI: 10.17755/esosder.468319
|View full text |Cite
|
Sign up to set email alerts
|

Seçmeni̇n Si̇yasal Reklamlara Yaklaşimi: Şüpheci̇li̇k Bakimindan Kuşaklar Arasi Bi̇r İnceleme

Abstract: Siyasal reklamcılık, siyasal parti veya adayın seçmen tarafından bilinirliliğinin arttırılması, seçmenin oy verme davranışına yöneltilmesi, verilmek istenilen mesajların kamuoyuna aktarılması ve kamuoyunun siyasi konularda bilgilendirilmesi için oldukça önemli bir kavramdır. Siyasal reklamlarda adayın veya partinin vaatlerine, politikalarına ve parti programlarına yer verilmekte, seçmen parti lehine ikna edilmeye çalışmaktadır. Şüphe ise; iknanın önündeki en büyük engellerden bir tanesidir. Seçmenlerin şüphe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, Ventura (2001) found that families transfer their political thoughts to their children and in this way, when their children come to voting age, they have the same political attitude and behaviour as their parents. Ay and Çağlar (2019) determined that digital marketing practices are effective on the political participation behaviours of Gen Y voters. Erdoğan (2019) determined that there is a significant difference between age groups in terms of voting behaviour.…”
Section: Hypothesis Development and Model Formationmentioning
confidence: 99%
“…Moreover, Ventura (2001) found that families transfer their political thoughts to their children and in this way, when their children come to voting age, they have the same political attitude and behaviour as their parents. Ay and Çağlar (2019) determined that digital marketing practices are effective on the political participation behaviours of Gen Y voters. Erdoğan (2019) determined that there is a significant difference between age groups in terms of voting behaviour.…”
Section: Hypothesis Development and Model Formationmentioning
confidence: 99%